Dual oxidation state tandem catalysis in the palladium-catalyzed isomerization of alkynyl epoxides to furans - Anderson, EA; Arroniz, C; Chaubet, G (American Chemical Society, 2018)
A two-catalyst system consisting of different oxidation states of palladium is described, which mediates the isomerization of alkynyl epoxides to furans. In a process termed “dual oxidation state tandem catalysis”, a multistep isomerization pathway is delineated in which the different metal oxidation states and ligands play independent mechanistic roles, but which, in combination, enable the use of milder reaction conditions and lower catalyst loadings than a single catalyst in isolation. In the present context, this rare example of a homobimetallic catalytic transformation provides a mild, scalable, and atom-efficient route for furan synthesis.